Microfungi associated with Pteroptyx bearni (coleoptera: lampyridae) eggs and larvae from Kawang River, Sabah (Northern Borneo) - Kevin Foo; Jaya Seelan Sathiya Seelan; Mahadimenakbar M. Dawood (MDPI, 2017)
Overlooking the importance of insect disease can have disastrous effects on insect conservation. This study reported the microfungi that infect Pteroptyx bearni eggs and larvae during ex-situ rearing project. Two different species of microfungi that infected the firefly’s immature life stages were isolated and identified. Penicillium citrinum infected the firefly’s eggs while Trichoderma harzianum infected the firefly during the larval stage. Both microfungi species caused absolute mortality once infection was observed; out of 244 individual eggs collected, 75 eggs (32.5%) were infected by Penicillium citrinum. All 13 larvae that hatched from the uninfected eggs were infected by Trichoderma harzianum. This study was the first to document the infection of Pteroptyx bearni’s eggs and larvae by Penicillium citrinum and Trichoderma harzianum.